2(y+2)=-2(y+5)

Simple and best practice solution for 2(y+2)=-2(y+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(y+2)=-2(y+5) equation:


Simplifying
2(y + 2) = -2(y + 5)

Reorder the terms:
2(2 + y) = -2(y + 5)
(2 * 2 + y * 2) = -2(y + 5)
(4 + 2y) = -2(y + 5)

Reorder the terms:
4 + 2y = -2(5 + y)
4 + 2y = (5 * -2 + y * -2)
4 + 2y = (-10 + -2y)

Solving
4 + 2y = -10 + -2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2y' to each side of the equation.
4 + 2y + 2y = -10 + -2y + 2y

Combine like terms: 2y + 2y = 4y
4 + 4y = -10 + -2y + 2y

Combine like terms: -2y + 2y = 0
4 + 4y = -10 + 0
4 + 4y = -10

Add '-4' to each side of the equation.
4 + -4 + 4y = -10 + -4

Combine like terms: 4 + -4 = 0
0 + 4y = -10 + -4
4y = -10 + -4

Combine like terms: -10 + -4 = -14
4y = -14

Divide each side by '4'.
y = -3.5

Simplifying
y = -3.5

See similar equations:

| 11sqrt(125)= | | 440=16t^2+4t | | 5x+-4=-9 | | 6x+4x-6+45=108 | | 20=1+3(x+8) | | r^4=-1 | | 9x-9=171 | | X/3-9=2 | | 7a+5=4a+10 | | -6(1-8k)+K=239 | | 8x-18-x-9= | | 7x+10=157 | | 7a+5=4 | | X/5-10=1 | | X/3=14/12 | | f(-2)=3x^2-5x+2 | | (5+37)+63=5+(37+63) | | 4n-7=9+7 | | 3(90-x)=180-x/3 | | 0=-0.1x^2+23x-1700 | | -16=4(x-3) | | (-3.4)-5/4 | | 6(4s+9)=294 | | 2y+5=6y+7 | | Y=1.5x-2.6 | | 15+6x=45x+8 | | 169+(x*x)=268.96 | | 8x+5=9x+9 | | -81=-3(-4x+5) | | 29-3m=-(m-8)+5 | | f(3)=3x^2-5x+2 | | c(c)-4c=0 |

Equations solver categories